Characterization of cellulose membranes modified with luminescent silicon quantum dots nanoparticles. (20th October 2016) - Campos, B.B.; Gelde, L.; Algarra, M.; Esteves da Silva, J.C.G.; Vázquez, M.I.; Benavente, J.
Highlights: SiQDs and SiQDs coated by PAMAM-OHG=5 dendrimer nanoparticles were successfully incorporate into a RC/4 membrane by dip coating. Characterized by thermal, luminescent and impedance spectroscopy. High thermal resistance, stable luminescent and conductive membranes were obtained. Abstract: A highly hydrophilic planar membrane fabricated with regenerated cellulose (RC-4 membrane), a biocompatible polymer, was modified by inclusion of water-soluble silicon quantum dot nanoparticles (SiQDs). Both bare SiQDs and SiQDs coated with a PAMAM-OH dendrimer were employed in order to obtain luminescent and thermally stable membrane systems (RC-4/SiQDs and RC-4/SiQDs-PAMAM-OH membranes). Original and SiQDs-modified membranes were characterized by fluorescence spectroscopy (steady and confocal), derivative thermogravimetric analysis and impedance spectroscopy measurements. According to these results, both SiQDs-regenerated cellulose composite membranes present luminescent character as well as higher thermal resistance and conductivity than the original sample, although the dendrimer coverage of the SiQDs might partially shield such effects. Moreover, the permanence of SiQDs nanoparticles in the structure of the cellulosic support in aqueous environments and their effect on diffusive transport were determined by water uptake as well as by membrane potential measurements at different concentrations of a model electrolyte (KCl). These results demonstrate the possible use of these stable nano-engineered membranes, which are based on SiQDs nanoparticles, in electrochemical devices under flow conditions.